Normative data for sweat rate and whole-body sodium concentration in athletes indigenous to tropical climate - Rivera-Brown, A. M.; Quiñones-González, J. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
This study determined normative data for sweat rate (SR) and whole-body (WB) sweat sodium concentration [Na+] in athletes indigenous to a tropical climate, categorized by age, gender, and sport classification. We analyzed data from 556 athletes (386 adult and 170 young) in endurance (END), team/ball (TBA), and combat (COM) sports exercising in tropical environments (wet bulb globe temperature = 29.4 ± 2.1 °C). SR was calculated from change in body weight corrected for urine output and fluid/food intake. Sweat was collected using absorbent patches, and regional [Na+] was determined using an ion selective analyzer and normalized to WB sweat [Na+]. Data are expressed as mean ± SD. SR was higher in males compared with females in both young (24.2 ± 7.7 ml/kg/hr vs. 16.7 ± 5.7 ml/kg/hr) and adult (22.8 ± 7.4 ml/kg/hr vs. 18.6 ± 7.0 ml/kg/hr) athletes, in END sports in girls (END = 19.1 ± 6.0 ml/kg/hr; TBA = 14.6 ± 4.5 ml/kg/hr), and in adult males (END = 25.2 ± 6.3 ml/kg/hr; TBA = 19.1 ± 7.2 ml/kg/hr; COM = 18.4 ± 8.5 ml/kg/hr) and females (END = 23.5 ± 5.6 ml/kg/hr; TBA = 14.2 ± 5.2 ml/kg/hr; COM = 15.3 ± 5.2 ml/kg/hr); p < .05. WB sweat [Na+] was higher in adult athletes than in young athletes (43 ± 10 mmol/L vs. 40 ± 9 mmol/L, p < .05). These norms provide a reference range for low, low average, average high, and high SR and WB sweat [Na+], which serve as a guide for fluid replacement for athletes who live and train in the tropics.